Exploring the factors influence halal food selection among Muslim youth while travelling - Fadzil, Nur Sakinah; Md Sawari, Siti Salwa (2019)
Halal industry has been commercialized by the Malaysian government for many years. Halal Industry Development Corporation (HDC) is part of the Malaysian government initiatives to facilitate the growth of Halal industry and it has been successfully stimulating Malaysian halal products in locally and globally (Aiedah, 2015). Although there were lots of efforts taken by the Malaysian government in commercializing the Halal food and brand, the consciousness of consuming the Halal food is still imprecise, especially among the young Muslim consumers. Thus, this study aims to investigate the factors influence Halal food selection among Muslim youth while traveling. A total of 384 respondents of Muslim youth consumers were participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 through several analyses such as descriptive analysis, frequency analysis, reliability analysis and multiple regression analysis. Results of this study indicated that religious beliefs, health reasons, and Halal logo and certificate affect Halal food selection among Muslim youth.